BOOK REVIEW OF LOVE STORY WRITTEN BY ERICH SEGAL - Handayani, Candra (LANTERN (Journal on English Language, Culture and Literature), 2015)
In this study, the writer will analyze the novel Love Story by Erich Segal by using the intrinsic theories. The purposes of this study are to analyze the main characters and toreveal the strengths and the weaknesses of Erich Segal‟s Love Story. Love Story tells aromantic story of two main characters, Oliver Barret IV and Jennifer Cavileri who arefrom different social and culture background. Although Love Story has some weaknesses,the strengths of this novel make it still be recommended to be read.